2011
DOI: 10.3354/dao02303
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of seven antiparasitics on Acolpenteron ureteroecetes (Dactylogyridae) from largemouth bass Micropterus salmoides (Centrarchidae)

Abstract: Few drugs are approved by the United States Food and Drug Administration for treating parasite infections in minor species such as fish, due in part to the high cost of developing such drugs and to a relatively small market share for drug sponsors. Because in vivo effectiveness trials for antiparasitic drugs are costly, time consuming, and use many animals, a systematic in vitro screening approach to describe parasite motility could help find promising drug candidates. We evaluated the effects of 7 antiparasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 121 publications
0
14
0
1
Order By: Relevance
“…No concentration of albendazole, fenbendazole, mebendazole or loperamide showed in vitro efficacy against N. buttnerae of C. macropomum, since they are poorly soluble in water, resulting therefore in variable and incomplete bioavailability (Ghanbarzadeh et al, 2016;Ibrahim & Al-Anazi, 2013;Pacheco et al, 2018;Romero, Navarro, Sanchez, & Valero, 2014;Taraschewski et al, 1990). Similar inefficacy of albendazole, fenbendazole and mebendazole has also been reported in relation to species of acanthocephalans, nematodes, monogeneans and trematodes parasitizing different fish species (Reimschuessel, Gieseker, & Poynton, 2011;Romero et al, 2014;Taraschewski et al, 1990;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…No concentration of albendazole, fenbendazole, mebendazole or loperamide showed in vitro efficacy against N. buttnerae of C. macropomum, since they are poorly soluble in water, resulting therefore in variable and incomplete bioavailability (Ghanbarzadeh et al, 2016;Ibrahim & Al-Anazi, 2013;Pacheco et al, 2018;Romero, Navarro, Sanchez, & Valero, 2014;Taraschewski et al, 1990). Similar inefficacy of albendazole, fenbendazole and mebendazole has also been reported in relation to species of acanthocephalans, nematodes, monogeneans and trematodes parasitizing different fish species (Reimschuessel, Gieseker, & Poynton, 2011;Romero et al, 2014;Taraschewski et al, 1990;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 67%
“…The acanthocephalan N. buttnerae of C. macropomum presented slow movements only after 6 hr of exposure to the highest concentrations of emamectin benzoate, ivermectin and praziquantel. Reimschuessel et al () also reported that there was a tardy response after in vitro exposure of Acolpenteron ureteroecetes Fischthal & Allison, 1940 to emamectin benzoate and ivermectin. However, Zhang et al () reported an immediate change in the movement of Dactylogyrus vastator Nybelin, 1924 after exposure to praziquantel.…”
Section: Introductionmentioning
confidence: 96%
“…2008;Horsberg 2012). Moreover, SLICE has been tested for controlling infections of the endoparasitic nematode Anguillicoloides crassus in freshwaterheld American Eels Anguilla rostrata (Larrat et al 2012), and EB has been tested for controlling infestations of two ectoparasitic crustacean copepods (Lernanthropus kroyeri in seawaterreared European Bass Morone [Dicentrarchus] labrax: Tokşen et al 2006; Caligus curtus in seawater-reared Atlantic Cod Gadus morhua: Hamre et al 2011) and for its in vitro effect against the endoparasitic monogenean Acolpenteron ureteroecetes collected from freshwater-reared Largemouth Bass Micropterus salmoides (Reimschuessel et al 2011).…”
mentioning
confidence: 99%
“…Praziquantel (PZQ: 2-cyclohexylcarbonyl-1, 2, 3, 6, 7, 11b-hexahydro-4H-pyrazino [2,1-a] iso-quinoline-4-one) is a broad-spectrum anthelmintic drug used in human and veterinary medicine. In aquaculture, PZQ is mainly used for controlling and killing acanthocephalans (Paterson et al 2013), trematodes (Kim & Cho 2000, Montero et al 2004, Mansell et al 2005, Reimschuessel et al 2011, cestodes (Pool 1985, Kline et al 2009, Iles et al 2012, and other parasites of fish. Although PZQ is applied widely in the treatment of aquatic animals, only a few studies have examined the pharmacokinetics and tissue residues of PZQ in fish (K. Kim et al 2001, C. Kim et al 2003, Tubbs & Tingle 2006a,b, Osman et al 2008, Xie et al 2015.…”
Section: Introductionmentioning
confidence: 99%